Experimental Study on the Impact of Thermal Maturity on Shale Microstructures Using Hydrous Pyrolysis - Liu, K.; Ostadhassan, M.; Hackley, P.C.; Gentzis, T.; Zou, Jie; Yuan, Yujie; Carvajal-Ortiz, H.; Rezaee, Reza; Bubach, B. (AMER CHEMICAL SOC, 2019)
Hydrous pyrolysis was applied to four low-maturity aliquots from the Utica, Excello, Monterey, and Niobrara Shale Formations in North America to create artificial maturation sequences, which could be used to study the impact of maturation on geochemical and microstructural properties. Modified Rock-Eval pyrolysis, reflectance, organic petrology, and Fourier transform infrared spectroscopy (FTIR) were employed to analyze their geochemical properties, while gas adsorption (CO2 and N2) was used to characterize their pore structures (pores < 200 nm). Organic petrography using white and blue light (fluorescence) before and after hydrous pyrolysis showed that amorphous organic matter cracked into solid bitumen, oil, and gas during hydrous pyrolysis. A reduction of the CH2/CH3 ratio in hydrous pyrolysis residues was observed from FTIR analysis. Rock-Eval pyrolysis showed that kerogens in the four samples were dissimilar, and hydrous pyrolysis residues showed smaller hydrogen index and Sh2 values than starting materials. Results from CO2 and N2 gas adsorption analysis showed that pore structures (micropore volume, micropore surface area, meso-macropore volume, and meso-macropore surface area) changed significantly during hydrous pyrolysis. However, changes in pore structure were dissimilar among the four samples, which was attributed to different activation energies of organic matter. A thermodynamic fractal model showed a decrease in fractal dimensions of Utica, Monterey, and Excello after hydrous pyrolysis, indicating a decrease in surface roughness. The pore size heterogeneity in the Utica sample increased as hydrous pyrolysis temperature increased, whereas the pore size heterogeneity distributions in the Monterey and Excello decreased based on the N2 adsorption data.